Clinical efficacy of p16/Ki-67 dual-stained cervical cytology in secondary prevention of cervical cancer - Celewicz, Aleksander; Celewicz, Marta; Wężowska, Małgorzata; Chudecka-Głaz, Anita; Menkiszak, Janusz; Urasińska, Elzbieta (Polish Journal of Pathology, 2018)
Cervical cancer is the third most common malignant neoplasm in women worldwide. HPV infection is the necessary factor for the cancer to develop. HPV DNA can be integrated into the genome of squamous epithelium and cause transcription of the viral oncoproteins and development of invasive cancer within 15-20 years. We assessed ICC co-expression of p16/Ki-67 proteins in smears collected from the uterine cervix and the association between p16/Ki-67 co-expression and cytologic and histologic results. Samples were collected from 93 women using liquid based cytology (LBC). Two microscopic slides were prepared: for Papanicolaou staining and ICC staining. Biopsy samples were collected from 43 women. Diagnosis of CIN 2+ was the endpoint of the study. p16/Ki-67 positive cells were found in women with: 1) a cytology result of ASC-US (3.59%), LSIL (2.22%), ASC-H (21.92%), HSIL (33.18%), SCC (72.22%) or NILM (3.44%); 2) a histopathologic result of CIN 1 (2.13%), CIN 2 (19.93%), CIN 3 (23.22%), SCC (69.72%) or normal histology (7.58%). p16/Ki-67 dual staining can increase the efficiency of screening methods and indicate women in whom further diagnostic procedures are required or those with extremely low risk of cancer. Sparing protocols will have a significant role in women of reproductive age.